Corilagin induces apoptosis and autophagy in NRF2-addicted U251 glioma cell line - Liu, Jilan (Mol Med Rep, 2021)
Corilagin, extracted from the Euphorbiaceae and Phyllanthus plants, inhibits the growth of a number of types of tumors. Compared with temozolomide, the traditional chemotherapy drug, corilagin has demonstrated stronger antitumor activity. However, the pharmaceutical mechanism of corilagin in glioma remains unclear. Nuclear factor erythroid 2 like 2 (NFE2L2 or NRF2) is positively associated with several types of tumor including glioma. In the present study, NRF2 expression was higher in glioma tissues compared with non-glioma specimens. Therefore, it was hypothesized that corilagin targets NRF2 regulation of U251 cell apoptosis. The present study used Hoechst 33258 staining to demonstrate that corilagin induced glioma cell apoptosis and observed that the expression of the apoptosis-related gene Bcl-2 was reduced. In addition, corilagin induced autophagy and promoted the conversion of light chain 3 (LC3) protein from LC3I to LC3II. NRF2 expression was downregulated by corilagin stimulation. Furthermore, the gene expression pattern following knockdown of NRF2 in U251 cells using siRNA was consistent with corilagin stimulation. Therefore, it was preliminarily concluded that corilagin induces apoptosis and autophagy by reducing NRF2 expression.